Analisis Faktor Penyebab Rendahnya Minat Belajar Siswa Terhadap Mata Pelajaran Matematika di MTs Ulul Albab - Cep Bambang Firdaus (Departement of Mathematics Education, 2019)
This study aims to analyze the factors that cause low interest in students' learning in mathematics at MTs Ulul Albab. The method used in the research is the survey method. The research technique was carried out by distributing questionnaires which were then analyzed descriptively. Questionnaire consists of 24 items related to 1) feelings (11 questions), 2) attention in learning (5 questions), and 3) interest in the material and the teacher (8 questions), with 2 alternative answers to the questionnaire namely